Evaluasi Penilaian Model Mini CEX pada Praktik Klinik Asuhan Kebidanan Komprehensif Continuity of Care - Christina Pernatun Kismoyo (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Mini CEX is an authentic assessment method, carried out in a clinic with direct clients and equipped withfeedback as a development for the next student's skills. Mini CEX has not been widely used in assessing theContinuity of Care Comprehensive Midwifery Clinical Practice. Evaluation is needed to see the suitability ofclinical assessment with reference standards. The aim of the study was to evaluate the mini CEX assessmentat the planning, implementation and outcome stages of the assessment. Descriptive evaluation research usingthe CIPP model. Taking a total sample of samples, a total of 176 respondents who were involved in midwiferyclinical practice activities in the Yogyakarta and Purworejo areas. Collecting data using a questionnaire thathas been tested for the validity of Aiken, all instruments are valid with a result of 0.75 (≥ 0.72). The evaluationresults of the assessment planning were very good (77.86%), the implementation by the preceptor was in thegood category (76%) and the assessment by the mentor was in the poor category (56%). Midwifery clinicalpractice assessment method using Mini CEX and feedback is concluded as good and can be continued.Instructor clinical input needs to be provided intensively or given CEX mini assessment training.Key words: evaluation, mini CEX, midwifery clinical practice